DETERMINING POPULATION TREND AND BREEDING BIOLOGY OF COMMON KESTREL (FALCO TINNUNCULUS) AT SIR BANI YAS ISLAND OF EMIRATES - B. Kabeer; S. Bilal; S. Abid; A. Mehmood; M. A. Asadi; M. J. Jilani; P. Hejcmanová (Journal of Animal and Plant Sciences, 2020)
Successful breeding is associated with propagation and well-being of the species and requires a healthy and intact ecosystem. However, to analyse these effects, the knowledge of the natural behaviours and variations in the breeding biology of the birds is essential. Common kestrel (Falco tinnunculus) is widely distributed in Asia, Africa and Europe. The current study was designed to evaluate the population trends and breeding success of common kestrel in Sir Bani Yas Island from 2014-2018, and to provide an insight to the survival of this species in a restored habitat. Population of common kestrel was monitored through line transect method by categorising it into three habitat types viz. Mountains, Forests, and Pastures/open area. In each habitat category, two transects of 2,000 meters length and 200 meters width on each side were laid. The population data from three habitat types showed statistically significant difference in preference of habitat types (H-Value = 27.43, DF = 2, P-Value = 0.0000011). The birds showed preference of open/pasture habitats in non-breeding season and mountains during breeding season. The courtship and nesting started during early April and the eggs were laid during late April. The average clutch size was 3.75 ± 0.31 eggs per clutch. The average incubation period was 29.13 ± 0.52 days resulting in average hatchlings of 3.50 ± 0.53 chicks. The eggs were incubated 74.02 ± 1.69 % and were unattended for 24.54 ± 1.64 % of the total incubation period. The finding of this study can be used as future reference to study the breeding success of the species and provide cues for further improvement of the ecosystem conditions by improving the habitat condition on the Island based ecosystems.
Keywords: Afforestation; Apex predators; Breeding Behaviour; Common Kestrel; Ecological health